P602 Factors associated with discontinuation of initial and subsequent tumour necrosis factor inhibitors in a large paediatric inflammatory bowel disease observational cohort. (16th January 2018) - Kaplan, J; Liu, C; King, E; Bass, J; Patel, A; Tomer, G; Tung, J; Pratt, J; Chen, S; Lissoos, T; Colletti, R; ,
Abstract: Background: Tumour necrosis factor inhibitors (TNFi) are effective in treating children with moderately to severely active ulcerative colitis (UC) and Crohn's disease (CD). However, nonresponse or loss of response to therapy may lead to sequential biologic treatment. Factors associated with TNFi discontinuation in children are not well known. The aim of this study was to assess for clinical factors associated with first and subsequent TNFi discontinuation in a large paediatric inflammatory bowel disease (IBD) cohort. Methods: We performed a retrospective study using data from ImproveCareNow (ICN), a multicentre, prospective paediatric IBD registry. Patients with CD and UC who were treated with their first TNFi after enrolment into ICN were identified at 39 participating ICN sites. Clinical information was obtained from the ICN database and chart review. The association of factors with TNFi discontinuation was assessed with Cox regression analysis. Results: Eight hundred and forty-six patients (678 CD, 168 UC) who fulfilled inclusion criteria were identified. Infliximab (IFX) was used first in 89% of CD patients, while 11% received adalimumab (ADA) first. On univariate analysis, discontinuation of the first TNFi in CD was associated with colonic only vs. ileocolonic disease location (hazard ratio (HR), 1.94; 95% confidence interval (CI), 1.28–2.94, p = 0.002) and higher shortPCDAI (HR, 1.01 per 1 unit increase in shortPCDAI; 95% CI 1.00–1.02, p = 0.032) and prednisone use (HR, 1.49; 95% CI 1.07–2.08, p = 0.017) at the time of TNFi initiation. Concomitant immunomodulator therapy was not shown to be associated with first TNFi discontinuation ( p = 0.23) (Figure 1). Discontinuation of the second TNFi (86% ADA, 14% IFX) in CD was associated with abnormal C-reactive protein (HR 3.33; 95% CI 1.05–10.55, p = 0.041), lower albumin ( p = 0.006) and haematocrit ( p = 0.032) at the time of second biologic initiation, and the presence of upper gastrointestinal (GI) tract CD (HR, 3.25; 95% CI 1.13–9.35, p = 0.029). IFX was used first in 94% of UC patients, while 6% received ADA first. Discontinuation of the first TNFi in UC was more common with ADA compared with IFX (HR, 2.43; 95% CI 1.02–5.80, p = 0.045). None of these clinical variables were significant in multivariable analysis. Conclusions: Multiple factors associated with TNFi discontinuation in paediatric IBD patients were identified, including colonic only and upper GI tract CD location as well as markers of more severe CD. Prospective studies are needed to confirm these findings.